2019
DOI: 10.1159/000499337
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Biopsy: General Concepts

Abstract: Liquid biopsy provides the opportunity of detecting, analyzing and monitoring cancer in various body effluents such as blood or urine instead of a fragment of cancer tissue. It is composed of different biological matrices such as circulating tumor cells (CTCs), cell free nucleic acids, exosomes or tumors “educated platelets.” In addition to representing a non- or minimally invasive procedure, it should represent a better view of tumor heterogeneity and allows for real-time monitoring of cancer evolution. Recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
154
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 247 publications
(172 citation statements)
references
References 59 publications
0
154
0
2
Order By: Relevance
“…Most biomarker research in cancer focus on quantifying genetic alterations within the tumor and tumor cells. Liquid biopsies are increasingly tested as novel cancer biomarkers by evaluating the so-called 'tumor circulome' consisting of circulating tumor nucleic acids (ctDNA and ctRNA), circulating tumor cells (CTCs), and tumor extracellular vesicles [1,2]. However, the potential of evaluating circulating proteins derived from the tumor microenvironment as novel liquid biopsies is undervalued.…”
Section: Introductionmentioning
confidence: 99%
“…Most biomarker research in cancer focus on quantifying genetic alterations within the tumor and tumor cells. Liquid biopsies are increasingly tested as novel cancer biomarkers by evaluating the so-called 'tumor circulome' consisting of circulating tumor nucleic acids (ctDNA and ctRNA), circulating tumor cells (CTCs), and tumor extracellular vesicles [1,2]. However, the potential of evaluating circulating proteins derived from the tumor microenvironment as novel liquid biopsies is undervalued.…”
Section: Introductionmentioning
confidence: 99%
“…Blood circulating biomarkers are currently used in research and have been suggested for tumor characterization to set a personalized target therapy [e.g., epidermal growth factor receptor (EGFR) mutation profile in lung carcinoma] in clinical practice. Despite the great development of droplet-based digital PCR (ddPCR) and the various optimizations of Next Generation Sequencing technologies (NGS), for both CTCs and ctDNA assays, there is no standardization starting from the pre-analytical phase through the analytical procedures to platform/technological methods [3][4][5] .…”
Section: Lb: Liquid Biopsy; Ec: Endometrial Cancermentioning
confidence: 99%
“…Firstly, and mainly, tissue samples might not fully represent tumor heterogeneity, constituting a limitation for accurate outcome prediction and treatment efficacy [5,6]. Moreover, early-stage tumor, residual disease, and early recurrence detection might be difficult, since tissue biopsy sampling requires a highly invasive intervention with risk of complications, and, depending on the tumor anatomical location, may be extremely difficult to obtain [4,7]. Therefore, a minimally invasive method that allows for cancer detection at an early stage and patients' follow-up is essential.…”
Section: Introductionmentioning
confidence: 99%